Marcophytobenhos of Beresansky Estuary, its costal waters and sea shore of Beresan Island - Tkachenko, F.P.; Artemenko, А.О. (M.G. Kholodny Institute of Botany, NAS of Ukraine, 2022)
The papers reports results of long-term monitoring of macrophytobenthos of the Beresansky Estuary and its coastal waters. The features of the distribution of macrophyte algae in the estuary and adjacent marine areas, including Berezan Island, were analyzed in connection with changes in their salinity and pollution. A total of 32 species of macrophyte algae from 4 divisions, 6 classes, 10 orders, 13 families and 17 genera were found in the Berezan Estuary. Chlorophyta (17 species) lead in species diversity, Rhodophyta (9) rank second, and Ochrophyta third (5). Charophyta were represented by one species. Both on the sea coast of the estuary and near the coast of Berezan Island, 13 species of macrophyte algae of almost identical composition were found, in particular, 8 species of green algae, 5 and 4 of red algae, respectively, and one species of brown algae. Increasing the salinity level of the Berezan Estuary by more than two times (up to 13.8‰) in recent decades caused changes in the species composition of the phytobenthos: charophytes and some freshwater green algae have disappeared, while marine red and brown algae have appeared.